Spectrum of mutations in patients with organic acidurias from Ukraine - Barvinska, O.I.; Olkhovych, N.V.; Shkurko, T.O.; Gorovenko, N.G. (Вiopolymers and Cell, 2018)
Aim. To identify mutations in patients from Ukraine with glutaric aciduria I, isolated methylmalonic aciduria, and isovaleric aciduria. Methods. Sanger sequencing. Results. We have identified 37.5 % of alleles (3/8) in patients with methylmalonic aciduria, 100 % of alleles (4/4) in patients with isovaleric aciduria, 100 % of alleles (4/4) in patients with glutaric aciduria type I. MUT gene mutations in patients from Ukraine are represented by one known N219Y missense mutation p. and a R326G missense rearrangement. Analysis of the GCDH gene in patients from Ukraine revealed three known missense mutations: R383C, G390R and A421V. Rearrangements in the IVD gene of our patients were represented by two novel mutations: 49dupTGTGGCG, S133C, and one known mutation: R53P. Conclusions. The mutations observed in Ukrainian patients with organic acidurias were mostly represented by rare or new rearrangements. These data could be useful for the development of molecular diagnostics of Ukrainian patients with glutaric aciduria I, isolated methylmalonic aciduria, and isovaleric aciduria